Legal Personhood for Artificial Intelligence: An Axiological Argument - Simanjuntak, Mardohar B. B.; Moeliono, Tristam P. (MELINTAS, 2025)
The growing autonomy of artificial intelligence systems challenges traditional legal doctrines that assume a strong connection between human agency and technological action. As AI increasingly operates within vehicles, robots, and decision-support infrastructures, harmful outcomes may arise from processes that no single human deliberately controls or can reasonably foresee. This dispersion of causation exposes responsibility gaps that liability, fault, and product-based frameworks are ill-equipped to resolve. Drawing on values central to legal and moral theory, this paper argues for a carefully circumscribed form of AI legal personhood as an instrumental tool for allocating responsibility in a coherent and ethically defensible manner. Even though instrumental personhood can appear counterintuitive to those who hold that recognition presupposes a degree of dignity that AI cannot possess, the analysis distinguishes intrinsic dignity from relational dignity and shows that our treatment of agent-like systems shapes the norms governing human interactions without attributing intrinsic worth to machines. Informed by Kurki’s modular theory of personhood and Harari’s analysis of algorithmic authority, a limited and function-specific legal status could enable autonomous systems to bear civil liability through mandatory insurance and operate as juridical nodes in tort and contract. This model preserves human oversight while acknowledging the de facto agency of advanced AI, thereby aligning responsibility with the technological locus of action and supporting frameworks for fair victim compensation, accountability, stability, and the reinforcement of societal values in environments increasingly shaped by autonomous systems. It is concluded that such a constrained form of AI personhood offers a principled and practical pathway for integrating autonomous systems into the legal order without eroding human dignity and welfare.